Communication Problems Experienced by African Graduate Students in Their Interaction with Malaysians in a Local University - Phang, Sce Hwai (2002)
The purpose of this qualitative case study was to explore the intercultural communication problems and difficulties experienced by African graduate students when they interact with Malaysians in a local public university in the Klang Valley, and how they cope with these problems. The study aimed to answer to three research questions: (a) What are the communication problems and difficulties faced by African students when interacting with Malaysians in the university? (b) What are the factors that contribute to the problems and difficulties? and (c) How do the international students cope with these problems? Data were collected from twelve African informants from Eastern and Western Africa and six Malaysians through semi-structured interviews and observation. There are three general conclusions derived from the findings of the study. The first conclusion is that the intercultural communication experience of the African students while interacting with Malaysians is problematic in nature. There are five categories of problems found in the interaction, namely: (a) Reservations towards foreigners; (b) Issue of greetings; (c) Indirectness; (d) Interrogations; and (e) Gender issues. The second conclusion of the study is that there are four possible factors that contribute to the communication problems and difficulties experienced by the African students in their interaction with the locals, which are: (a) Cultural differences; (b) Language; (c) Prejudices and Stereotypes; and (e) Limited exposure to Africans. And the final conclusion is that the Africans use two coping strategies to regulate the psychological discomfort and stress when encountering these difficulties - problem-focused and emotion-focused strategies. The problem-focused strategies include active coping, restraint coping, confrontive coping, and seeking instrumental social support. The emotion-focused strategies include acceptance, positive reinterpretation and growth, self-control, seeking emotional social support, distancing, and behavioural disengagement.